The Network of Tumor Microtubes: An Improperly Reactivated Neural Cell Network With Stemness Feature for Resistance and Recurrence in Gliomas - Wang, Xinyue; Liang, Jianhao; Sun, Haitao (Frontiers in Oncology, 2022)
Gliomas are known as an incurable brain tumor for the poor prognosis and robust recurrence. In recent years, a cellular subpopulation with tumor microtubes (TMs) was identified in brain tumors, which may provide a new angle to explain the invasion, resistance, recurrence, and heterogeneity of gliomas. Recently, it was demonstrated that the cell subpopulation also expresses neural stem cell markers and shares a lot of features with both immature neurons and cancer stem cells and may be seen as an improperly reactivated neural cell network with a stemness feature at later time points of life. TMs may also provide a new angle to understand the resistance and recurrence mechanisms of glioma stem cells. In this review, we innovatively focus on the common features between TMs and sprouting axons in morphology, formation, and function. Additionally, we summarized the recent progress in the resistance and recurrence mechanisms of gliomas with TMs and explained the incurability and heterogeneity in gliomas with TMs. Moreover, we discussed the recently discovered overlap between cancer stem cells and TM-positive glioma cells, which may contribute to the understanding of resistant glioma cell subpopulation and the exploration of the new potential therapeutic target for gliomas.